Perbaikan Mutu Layanan Toko Mini Swalayan Menggunakan Pendekatan Fuzzy Quality Function Deployment - Rohmatulloh Rohmatulloh; Marimin Marimin (Universitas Bunda Mulia, 2017)
The application of service quality in modern retail business using quality function deployment (QFD) described on this paper. This study was developed at Mini Market Tipar Cakung. QFD, as known as house of quality, is applicable in multi-sectors business and an excellent tool for management to form a customer-mapping and developing customer requirements prioritization and also translate them into internal technical response system. The scoring, to determine important customer requirements, used pair wise comparisons scoring method (analytical hierarchy process). Fuzzy scoring for linguistic term was proposed on relationship matrix to determine the most important ones depending on the company’s own condition. This study shows that the most important improvement of service quality is based on economic motive.Keywords: Quality Function Deployment, Fuzzy Relationship Matrix, Mini Market